Avoidance of "Final" Surgical Fusion After Growing-Rod Treatment for Early-Onset Scoliosis. (6th July 2016) - Jain, Amit; Sponseller, Paul D.; Flynn, John M.; Shah, Suken A.; Thompson, George H.; Emans, John B.; Pawelek, Jeff B.; Akbarnia, Behrooz A.
Abstract : Background: Definitive "final" surgical fusion is the common end point for growing-rod treatment of early-onset scoliosis. However, final surgical fusion may be unnecessary for patients who have reached skeletal maturity with good alignment. This study characterizes patients who completed growing-rod treatment but did not undergo final surgical fusion. Methods: Using a multicenter early-onset-scoliosis database, we identified 167 patients who received growing-rod treatment from 1995 through 2010, reached skeletal maturity, and had a minimum 2-year follow-up after their last surgery. Thirty patients did not undergo final surgical fusion (observation group) and were compared clinically and radiographically with 137 patients who did undergo final fusion (final surgical fusion group). Results: No significant differences were found between the groups with regard to the age at which treatment was initiated (p = 0.127), distribution of diagnoses (p = 0.84), or number of lengthening procedures (p = 0.692). In the observation group, 26 patients retained the growing rods and 4 patients had them removed at the last surgery because of infection. The mean primary curve correction at the end of treatment was 48% (from an initial mean magnitude of 79° to a mean final curve of 41°) in the observation group compared with 38% (from 74° to 46°) in the final surgical fusion group. There was no significant difference in final curve magnitude (41° in the observation group and 46° in the final surgical fusion group; p = 0.182). The mean increase in trunk height was 30.5% in the observation group and 35% in the final surgical fusion group. The final trunk height in the observation group was not significantly less than that in the final surgical fusion group (p = 0.142). Conclusions: Because of progressive ankylosis, avoiding final surgical fusion at skeletal maturity is a viable option for patients treated with growing rods for all diagnostic subgroups of early-onset scoliosis who have satisfactory final alignment and trunk height, a minimal gain in length at the last distraction, and no clinical or radiographic evidence of implant-related problems. Level of Evidence: TherapeuticLevel III . See Instructions for Authors for a complete description of levels of evidence.